A new species of Phenacorhamdia (Siluriformes: Heptapteridae) from the Juruena River basin, with insights into its phylogenetic position - Silva, Gabriel S. C.; Castro, Íthalo Da Silva; Ohara, Willian Massaharu; Oliveira, Claudio (Zootaxa, 2024)
Heptapteridae is a group of small to medium-sized neotropical catfish composed of 23 genera and 238 valid species, classified into two subfamilies: Rhamdiinae and Heptapterinae. Phenacorhamdia represents small heptapterids and is composed of 14 valid species distributed across all major river basins in South America. In this paper, we add another species to the genus, described from the Juruena River basin, Mato Grosso state, Central Brazil. This species is distinguished from its congeners by having multicuspid teeth, 47–52 vertebrae, maxillary barbel not reaching to pectoral-fin origin, and absence of a short extension of the first pectoral-fin ray. Additionally, a brief discussion on its putative phylogenetic position, based on UCEs dataset, is provided.